Robust Hybrid Controller Design to Stabilise an Underactuated Robot Vehicle under Various Input. (16th November 2022) - Hussein, Yomna Sabah; Kamil, Haider Galil; Al-Moadhen, Ahmed Abdulhadi
Abstract : This paper presents the design of the control system for a robot vehicle with two wheels that mimics a double Inverted Pendulum (IP) system with an extendable payload. By expanding the degrees of freedom, the system is more flexible. Still, this model posed challenges for control of parts of the system, including the proper balancing of the intermediate body and angular displacement of both wheels and lifting the payload to the demanded height. In this paper, a hybrid control system that incorporates more than one type of controller which combined proportional integral derivative (PID), proportional derivative (PD), and fuzzy logic control (FLC) these controllers are designed for stabilising the aforementioned system. The controller was validated by applying different input signals to the payload actuator to prove the control system's stability and analyse the system's behaviour. The simulation results were satisfactory for the hybrid control technique. The wheels successfully stabilised within 1.2682 s. Further, the first and second links stabilised at 9.5953 s and 9.6467 s, respectively. The payload approximately produces the same input signal applied to the payload actuator. The model was derived using the Euler–Lagrange equation. The equations are solved using kinetic energy and potential energy which employs for motion. Simulation results of the two-wheeled robot vehicle with extendable payload designed with hybrid control systems are implemented using MATLAB/Simulink environment.